2019
DOI: 10.1021/acsnano.9b04148
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coiled-Coil-like Assembly by Knob-into-Hole Packing of Single Heptad Repeat

Abstract: Coiled-coil peptides represent the principal building blocks for structure-based design of bionanomaterials. The sequence–structure relationship and precise nanoscale ordering of the coiled-coil helices originate from the knob-into-hole (KIH) packing of side chains. The helical interface stabilized by the KIH interaction is known to have chain lengths ranging from 30 to 1000 residues. Yet the shortest peptide required for oligomerization through KIH assembly is still unknown. Here, we report that through atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Apart from the better helicity, our simulations further suggested that the long linker in the App substituent may also permit better intermolecular aromatic stacking of the Ph groups. In contrast, the formation of aromatic packing between Phe/Hpa side chains would be incompatible to the helical conformation of backbone, consistent with previous reports (18). Together, the current findings above add a crucial layer of details to our understanding of the substitution effects on the self-assembly of ultrashort helical peptides.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Apart from the better helicity, our simulations further suggested that the long linker in the App substituent may also permit better intermolecular aromatic stacking of the Ph groups. In contrast, the formation of aromatic packing between Phe/Hpa side chains would be incompatible to the helical conformation of backbone, consistent with previous reports (18). Together, the current findings above add a crucial layer of details to our understanding of the substitution effects on the self-assembly of ultrashort helical peptides.…”
Section: Discussionsupporting
confidence: 91%
“…The combination of self-assembly simulations and various spectroscopic characterizations also offered molecular insights into the self-assembly behavior of this peptide and its organization into fibers. The overall molecular architecture of the fibers formed by our stapled peptides was similar to those formed by other short peptides (14,18,34). The peptides stacked on top of one another in a headto-tail manner, forming helical columns that further assembled laterally.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Furthermore, this super helical arrangement of the peptide produced supramolecular rod‐like nanofibers at low pH, followed by lyotropic liquid crystals with predictable thermotropic properties. [ 79 ]…”
Section: Supramolecular Assembly Of Peptides Containing 2‐amino Isobutyric Acidmentioning
confidence: 99%